Patients’Perceptions of Having a Good Life One Year after Arthritis Patient Education: A Qualitative Study Nested within a Randomized Controlled Trial - Steinsbekk, Aslak; Grønning, Kjersti; Bratås, Ola (Department of Nursing, Faculty of Medicine, Diponegoro University, 2017)
Background: Patients with inflammatory polyarthritis have various degrees of disease-related challenges such as joint pain, stiffness, fatigue, and physical limitations. Despite these challenges, patients strive for a good life using their personal resources, often taught in patient education. The effect of patient education in polyarthritis is well studied; however, long-term studies on what patients perceive as a good life after participating in arthritis patient education are scarce.Purpose: The aim of this study was to explore patients’ perceptions of having a good life one year after attending a nurse-led patient education intervention.Methods: This was a qualitative study nested within a randomized controlled trial (RCT) studying the effect of nurse-led patient education. Fifteen individual semi-structured interviews were conducted among those who attended the nurse-led patient education intervention. The intervention focused on the consequences of living with chronic inflammatory arthritis. The interviews explored how and whether the intervention had made any changes in the informants perceived health, well-being, arthritis, flares, and treatment regimes. The data were analyzed thematically using systematic text condensation.Results: The findings showed that the informants’ perceptions of having a good life were related to a stable disease with few symptoms, effective treatment regimes, discovering new opportunities and perspectives in life, as well as making choices that felt right. Creating a good life was something the informants had acquired knowledge about in the nurse-led patient education intervention, particularly in the part where they had discussed and shared experiences with each other on how they managed their arthritis in different ways and settings.Conclusion: Participating in a nurse-led patient education intervention in arthritis helped the informants to discover new opportunities and perspectives on creating a good life, especially through exchanging experiences with fellow patients.